PERAN ORGANIZATIONAL CITIZENSHIP BEHAVIOR SEBAGAI PEMEDIASI PENGARUH KEPUASAN KERJA TERHADAP KINERJA PERAWAT - Ritonga, Eny (Fakultas Ekonomi, UIN Maliki Malang, 2018)
Abstract: The increasingly tight competition especially in the field of service in hospital business where everyone is tying for maintain their existence within the scope of the organization. The focus of this research was to analyze the direct and indirect influence of job satisfaction on employee performance, and the role of OCB as the mediator of job satisfaction on the performance of RSI Aisyiyah Malang employees. The approach used in this research was quantitative approach.The sample collection technique used was simple random sampling. The sample in this study amounted to 61 employees of RSI Aisyiyah Malang nurses. Data collection was using questionnaires, while data analysis was done by using path analysis. The results showed that 1) there was a direct effect of job satisfaction on employee performance of RSI Aisyiyah Malang nurses. This meant that the performance of RSI Aisyiyah nurses was better if job satisfaction felt by the nurses was better too. 2) there was indirect effect of job satisfaction on employee performance of RSI Aisyiyah Malang. 3) OCB mediated the influence of job satisfaction on employee performance of RSI Aisyiyah Malang. Â Â Keywords: Job Satisfaction, Employee Performance, and Organizational Citizenship Behavior